(untitled) (Global Journals of Research in Engineering, 2012)
Orthogonal Frequency Division Multiplexing OFDM is a promising technique for high data rate wireless communications because it can combat inter-symbol interference caused by the dispersive fading of wireless channels A FDM channel is like water flow out of a faucet in contrast the OFDM signal is like a shower In a faucet all water comes in one big stream and cannot be subdivided OFDM shower is made up of a lot of little streams The demand for high speed mobile wireless communications is rapidly growing OFDM technology promises to be a key technique for achieving the high data rate capacity and spectral efficiency requirements for wireless communications of the near future which was a source of motivation for this project Here in this paper we simulate a cyclic prefix OFDM system with Binary Phase Shift Keying Modulation on each subcarrier CP-OFDM system includes a repetition code and interleaving across subcarriers as well as a Rayleigh fading channel model with exponentially decaying power profile